Studies of nonlinear hydrodynamics based on moving particles semi-implicit method: development and applications. - Cezar Augusto Bellezi (2019)
The present work is focused on the development and application of the Moving Particles Semi-Implicit (MPS) method to the investigation of complex nonlinear hydrodynamics problems in naval and offshore engineering. This work is divided into three different studies that share this background and each one presents its own original contribution: PART 1: The first study consists in the proposal of a perforated swash bulkhead with optimized geometry in order to mitigate the sloshing in rectangular tanks. The first step of the investigation comprises the assessment of the effects of the bulkhead openarea ratio in the sloshing flow based on a comprehensive parameter analysis. Then, a function of the optimized open-area ratio as function of the filling ratio is proposed. Three different swash bulkhead models with optimized geometry are evaluated and successfully mitigated the sloshing resonance in the frequency range encompassing the three first sloshing resonant modes for different filling ratios. This investigation resulted in technological innovation, as a highly effective engineering solution with simple implementation was achieved. PART 2: In the second study, the resonance within narrow gaps between naval and offshore structures is investigated by MPS simulations. It consists on a parameter analysis of a simplified two-dimensional barge with imposed harmonic sway motion. Different widths of the gap, motion frequencies and amplitudes were considered. Two different resonant modes in the gap were observed from the particle-based simulations: the piston-mode and the sloshing-mode. In particular, two peaks in the frequency domain were observed for the piston-mode resonant flow. The behavior of the second peak resembled a syphon U-tube flow and it was not previously reported in the literature. Then, two simple mechanical models, with 1 DOF and 2 DOF were adopted in order to explain these two peaks. PART 3: In the third study of this thesis, a multiresolution technique called \"border mapping\" is proposed for the MPS method. The border mapping technique aims to obtain an \"equivalent particle distribution\" in the truncated boundary between two sub-domains with different resolutions and it is divided into two steps: the refinement of the coarse region of the border and the simplification of the fine region of the border. The main aspect of the proposed approach is to use the actual irregular particle distribution in the border region, which enhances the numerical stability. The preliminary tests of the proposed technique were promising, as the pressure was correctly calculated, the mass of the system was properly conserved and the computational cost could be substantially reduced in relation to a single-resolution simulation. This study is a contribution to the state-of-the-art of the meshless methods in computational fluid dynamics.